The Importance of Standardization in Biometric Data for Digital Forensics - Ulupinar, Semih; Dogan, Sengul; Akbal, Erhan; Tuncer, Turker (Ieee, 2017)
Digital forensics is a multi-disciplinary science area that sets standards for the collection, storage, compilation and analysis of electronic data. To evaluate data in judicial information, the evidence must have certain standards. The evidence includes many types of data such as audio, video and text that exist in electronic devices. Especially biometric data that contain specific information about the person have a large share in assessing cases in the field of digital forensics. In this paper, standardization process of biometric data is presented. At the same time, the standardization of biometric data has been examined in terms of digital forensics.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: biometry; biometric systems; standardization; digital forensics